Association of periodontal disease with breed size, breed, weight, and age in pure-bred client-owned dogs in the United States. (September 2021) - Wallis, C.; Saito, E.K.; Salt, C.; Holcombe, L.J.; Desforges, N.G.
Highlights: Over 3 million pet records analysed showing differences in periodontal disease risk. The majority of dogs diagnosed with periodontal disease weighed under 15 kg. Risk factors include age, being overweight, and time since last scale and polish. Highlights dogs most at risk on which diagnostic efforts should be focussed. Abstract: Despite periodontal disease (PD) being amongst the most common diagnoses in primary-care practice, the disease is generally underdiagnosed. However, the millions of clinical records generated by pet hospitals each year provide unique opportunities to generate insights about disease risk across large numbers of dogs. The objective of this study was to undertake a retrospective analysis of medical records to ascertain which sizes and breeds of dog are most frequently diagnosed with PD. Although data collection regarding PD was not consistent, it was assumed that the same inconsistencies in recording periodontal abnormalities were present across the range of bodyweight, breed categories and breeds. Over 3 million medical records across 60 breeds of dogs visiting a chain of veterinary hospitals in the United States collected over a 5-year period were analysed. Statistical analysis of a subset of these records found that extra-small (<6.5 kg) breeds of dog were up to five times more likely to be diagnosed with PD than giant breeds (>25 kg) ( P <0.0001). The majority of breeds most frequently diagnosed with PD were in the extra-small, small (6.5−9 kg) and medium-small (9−15 kg) breed size categories. Additional risk factors for PD diagnosis included age, being overweight and time since last scale and polish. Veterinarians should consider targeting client education about dental health, and diagnostic efforts, towards canine patients of the small-breed size categories and those with a higher risk of developing PD (e.g. overweight).